Feasibility and antihypertensive effect of replacing regular salt with mineral salt -rich in magnesium and potassium- in subjects with mildly elevated blood pressure - Sarkkinen, Essi S (BioMed Central, 2011)
BACKGROUND: High salt intake is linked to hypertension whereas a restriction of dietary salt lowers blood pressure (BP). Substituting potassium and/or magnesium salts for sodium chloride (NaCl) may enhance the feasibility of salt restriction and lower blood pressure beyond the sodium reduction alone. The aim of this study was to determine the feasibility and effect on blood pressure of replacing NaCl (Regular salt) with a novel mineral salt [50% sodium chloride and rich in potassium chloride (25%), magnesium ammonium potassium chloride, hydrate (25%)] (Smart Salt). METHODS: A randomized, double-blind, placebo-controlled study was conducted with an intervention period of 8-weeks in subjects (n = 45) with systolic (S)BP 130-159 mmHg and/or diastolic (D)BP 85-99 mmHg. During the intervention period, subjects consumed processed foods salted with either NaCl or Smart Salt. The primary endpoint was the change in SBP. Secondary endpoints were changes in DBP, daily urine excretion of sodium (24-h dU-Na), potassium (dU-K) and magnesium (dU-Mg). RESULTS: 24-h dU-Na decreased significantly in the Smart Salt group (-29.8 mmol; p = 0.012) and remained unchanged in the control group: resulting in a 3.3 g difference in NaCl intake between the groups. Replacement of NaCl with Smart Salt resulted in a significant reduction in SBP over 8 weeks (-7.5 mmHg; p = 0.016). SBP increased (+3.8 mmHg, p = 0.072) slightly in the Regular salt group. The difference in the change of SBP between study groups was significant (p < 0.002). CONCLUSIONS: The substitution of Smart Salt for Regular salt in subjects with high normal or mildly elevated BP resulted in a significant reduction in their daily sodium intake as well as a reduction in SBP. TRIAL REGISTRATION: ISRCTN: ISRCTN01739816